(untitled) (Malaysian Management Journal, 2003)
This article is intended to provide several case studies of successful waste management of a few selected industries in their attempts to become â€œenvironmental-consciousâ€ firms. In particular, this article examines the innovative waste-reduction and waste reuse processes undertaken by certain firms in the following industries - asphalt cement and concrete, ferrous metals, Portland cement and concrete, and some other that on the face of it somewhat isolated innovative technologies. For each case, the driver, the waste management technology or processes involved, as well as the associated economic benefits of the adjustments was highlighted. It is hoped that the findings of this article will provide the motivation or continue to motivate engineers and scientists to further explore processes that will help towards better management of industrial wastes.